Developing young minds : from conception to kindergarten - Shore, Rebecca, 1957- (Lanham, Maryland : Rowman & Littlefield, 2015)
Ever wonder what is going on in a baby's brain? Or how you can best nurture a child's natural development? Or why exactly Bach is better than Mozart for babies? This book will explain why. No technical knowledge is necessary, as Shore makes recent neurological findings accessible to all those who come into contact with young children. Everything a baby experiences in his or her first five years is building the foundation of life's learning potential. Through increasing the complexity of the early childhood environment in developmentally appropriate ways, we can nurture young children's brains. Developing Young Minds is a must-have for new parents or caregivers of young children.--From Amazon.com.
Finding faulty assumptions -- Brain science for non-neurologists -- How we know what we know -- Nurturing our nature -- Arts smarts -- Music matters -- The Bach effect -- Implications for education -- Curricular considerations -- Creating complex curriculum for the crib and beyond.
Includes bibliographical references and index.
Keywords: Early childhood education; Child development; Thought and thinking -- Study and teaching (Early childhood); Cognition in children; Learning, Psychology of; Brain